دور شركة العنان بين مقاصد الأموال وإدارة الأعمال: دراسة تحليلية وصفية = The role of Sharikah al-ʿAnān (cooperative partnership) between property goals and work management: an analytical-descriptive study - Eletrebi, Mohamed Fathy; Suleiman, Hassan (Intelligentia Resources, 2022)
The study aims at an analytical-descriptive study of the role of Sharikah al-ʿAnān’s (Cooperative Partnership) in the movement of funds as it is considered one of the companies agreed upon by the jurists, with an emphasis on the flexibility of Islamic jurisprudence in dealing with the contemporary issues and developments of work management. This is by standing on the ruling of cooperative partnership and some of its contemporary applications, and commercial transactions between partners, while dealing with the nature of the sharikah and its financial implications. This paper discussed the problematic jurisprudential difference regarding the cooperative partnership as a contemporary transaction, and the reason for this problem, and the method of jurisprudential adaptation of this difference. This study took the descriptive-analytical approach as a method for study and consideration. The research reached several conclusions, including: The underlying reason for the legality of the company and its intended types is to enable people to cooperate in righteousness and piety through mutually beneficial and profitable work based on the difference between people’s in divine talents and human capabilities. There are many divisions of sharikāt in Islamic jurisprudence, including the property company, contracts, organizations, cooperatives, perspectives, speculations, which indicates the flexibility and vitality of jurisprudence. All fuqahas and scholars agree that al-ʿAnān’s company or Sharikah al-ʿAnān is permissible, despite their differences in opinion regarding certain of its term and condition; logically, two people share their money in accordance with the terms of their contract and engage in commerce with the profit divided between them. Regarding the management of the company between the two partners, the general rule is that neither partner may dispose of the other’s money after the contract without the other’s consent, nor may he withdraw anything from it without the other’s consent.